Transformation in love in Paul's letter to the Galatians - Pieter G. R. de Villiers (Acta Theologica)
Paul’s Letter to the Galatians is known as a bitter defence of his “true” gospel of faith against opponents who wish to impose their “false” gospel of works on the faith community. This focus on the faith-works controversy has not been conducive to attempts to read it in terms of the notion of love. This article seeks to reconsider this position and to spell out the special role of love in the letter and its transformative nature. In a first section, the approach to the theme is explained. After a discussion of the polemical nature of the letter, the article analyses Paul’s presentation of divine love in the letter as the origin of God’s salvific and transformative action and of love as a divine characteristic, and how divine love marks the identity of the believing community. The significance of love in the ethos and ethics of the faith community is spelled out.